2017
DOI: 10.18203/2349-2902.isj20172385
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic bile duct injury repair using isolated vascularized gastric tube: early experience in two tertiary centers

Abstract: INTRODUCTIONAbout 80% of BDI occur after cholecystectomy constituting a catastrophe for both the patient and the surgeon as they are associated with significant morbidity and mortality, reducing long-term survival and quality of life, and are associated with high rates of subsequent litigation.1,2 Laparoscopic cholecystectomy (LC) has largely replaced open cholecystectomy (OC) but its potential disadvantage is a 2-fold increase in BDI. Moreover, injuries after LC are more proximal, are revealed earlier, are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…A wide variety of surgical procedures with biliary access handles have been performed in order to facilitate endoscopic approaches, and for this reason many authors have attempted to design a series of procedures. Barker and Winkler 20 published an additional procedure to hepaticojejunostomy, taking the end of the proximal handle of the Roux-in-Y to the abdominal wall, building a jejunum stoma in the right subcostal area of the abdominal wallHelmy, et al 9,21 report the use of a pedicle gastric tube lodged between the proximal and distal segments of the injured biliary ducts, in a first clinical case, with positive results at the time of the 5-month follow up, and a series of 18 cases with injuries and loss of segment after 2 years without complications. They concluded that it has advantages over other procedures because the functional sphincter of Oddi is preserved, facilitating diagnostics and therapeutic procedures, such as the endoscopic retrograde choliopancreatography, which has been proven to be extremely difficult after a Rouxin-Y hepaticojejuno anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of surgical procedures with biliary access handles have been performed in order to facilitate endoscopic approaches, and for this reason many authors have attempted to design a series of procedures. Barker and Winkler 20 published an additional procedure to hepaticojejunostomy, taking the end of the proximal handle of the Roux-in-Y to the abdominal wall, building a jejunum stoma in the right subcostal area of the abdominal wallHelmy, et al 9,21 report the use of a pedicle gastric tube lodged between the proximal and distal segments of the injured biliary ducts, in a first clinical case, with positive results at the time of the 5-month follow up, and a series of 18 cases with injuries and loss of segment after 2 years without complications. They concluded that it has advantages over other procedures because the functional sphincter of Oddi is preserved, facilitating diagnostics and therapeutic procedures, such as the endoscopic retrograde choliopancreatography, which has been proven to be extremely difficult after a Rouxin-Y hepaticojejuno anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Helmy et al had a cohort of 18 adult patients who mainly had IVGT grafts for bile duct injuries [9]. It is important to note that they used a trans-anastomotic stent within the graft, and one stent was blocked postoperatively and had to be removed.…”
Section: Discussionmentioning
confidence: 99%
“…Helmy et al published a study using an isolated vascularized gastric tube (IVGT) graft as a biliary conduit in 2011 [8]. The IVGT graft was later successfully adapted for adult patients with common bile duct injuries [9]. Given the concerns regarding RYBD, children's long life expectancy and the lack of interventional radiological services, we have adopted IVGT graft as a primary reconstructive procedure for our paediatric patients at our institution and review our experience.…”
Section: Introductionmentioning
confidence: 99%
“…Barker y Winkler 20 publicaron un procedimiento adicional a la hepático-yeyunostomía, llevando la parte terminal del asa proximal de la Y de Roux a la pared abdominal, construyendo un estoma de yeyuno en el área subcostal derecha de la pared abdominal. Helmy, et al 9,21 reportan el uso de un tubo gástrico pediculado interpuesto entre los segmentos proximal y distal de la vía biliar lesionada, en un primer caso clínico, con buenos resultados en un seguimiento de 5 meses, y una serie de 18 casos con lesiones y pérdida de segmento con un seguimiento a 2 años sin complicaciones. Consideran que tiene ventajas sobre otros métodos porque se preserva el esfínter de Oddi funcional, facilitando procedimientos diagnósticos y terapéuticos como la colangiopancreatografía retrógrada endoscópica, la cual ha probado ser sumamente difícil después de una anastomosis hepático-yeyuno en Y de Roux.…”
Section: Discussionunclassified